Analisis Determinan Sosiodemografi dan Perilaku Terkait Kejadian Servisitis dalam Kehamilan: Tinjauan Sistematik - Kencana, Nabila Safhira Titan; Prakoeswa, Flora Ramona Sigit; Pramuningtyas, Ratih; Soekiswati, Siti; Dzikri, Dykall Naf’an (Cermin Dunia Kedokteran, 2026)
Introduction: Cervicitis is an inflammation of the cervix that can lead to serious complications during pregnancy. The objective of this article is to identify risk factors associated with the incidence of cervicitis in pregnant women. Methods: Literature review with narrative analysis. Article searches were conducted on the ScienceDirect, Sage, Google Scholar, and Garuda databases using predetermined keywords. A total of 2,009 articles were obtained from the 4 databases. After the screening process based on the inclusion and exclusion criteria, 15 articles were obtained for analysis. Results: Analysis of 15 articles showed that the incidence of cervicitis in pregnant women is influenced by several risk factors, including: (1) Demographic characteristics such as age and ethnicity; (2) Behavior and lifestyle including sexual intercourse and smoking patterns; (3) Obstetric and gynecological health history; (4) Socio-economic factors; (5) Living environment; and (6) Personal hygiene. The most consistently reported factors were poor personal hygiene, low socioeconomic status, and risky sexual behavior. Conclusion: Cervicitis in pregnant women is associated with complex and multidimensional risk factors. Identification of these factors is important for developing prevention and early detection strategies, thereby reducing the incidence of cervicitis and preventing serious pregnancy complications.